Cash waqf risk management and perpetuity restriction conundrum - Azniza Hartini Azrai Azaimi Ambrose; Fadhilah Abdullah Asuhaimi (ISRA International Journal of Islamic Finance, 2021)
Purpose - The purpose of this paper is to comprehensively discuss the issue of risk vis-à-vis the perpetuity restriction principle inherent in waqf (Islamic endowment). Specifically, it attempts to consolidate the axioms in both conventional and Islamic finance, such as the risk-return trade-off and al-ghunm bi al-ghurm (liability accompanies gain), with the perpetual nature of waqf. Overall, this paper attempts to find a resolution to the dilemma of perpetuity restriction inherent in cash waqf against the natural occurrence of the risk. Design/methodology/approach - This paper is based on the secondary research methodology; past literature encompassing journal articles, books, relevant financial axioms, fatwas (Islamic rulings) and state enactments is critically reviewed to present its case. In regard to state enactments, only Malaysian state enactments have been used, thus restricting the study to the Malaysian case only. Findings - This study contends that the dilemma of the perpetuity restriction and the natural occurrence of risk can be resolved through the integration of waqf risk management, especially concerning cash waqf, with the Islamic spiritual approach. By implementing standard operating procedures that inculcate awareness on waqf risk management and Islamic spirituality in waqf stakeholders (waqif (donor), trustee and beneficiaries), the stakeholders may accept the reality of risk that is inevitable even after all efforts have been exhausted. In other words, the violation of perpetuity is exonerated given that mental faculties aligned with revealed texts have been exhaustively used beforehand. Practical implications - Findings from this study may broaden the choice of investment avenues for waqf trustees while adhering to the perpetual restriction of waqf. More importantly, waqf trustees will not be forced to invest in interest-bearing securities or be involved in any usurious transactions just to obtain guaranteed returns and preserve the corpus of waqf. Originality/value - This study offers a unique perspective on cash waqf risk management by reanalyizing the axioms and concepts of finance and waqf while observing the welfare of the beneficiaries.
Keywords: 330; Cash waqf; Irrevocable waqf; Islamic endowment; Islamic finance; Temporary waqf; Waqf